Height versus weight which cassel parameter determine pulmonary functions fitness among the Algerians soccer players - Zerf Mohammed, Houar Abelatif, Mime Mokhtar, Bengoua Ali (J Pulm Respir Med, 2016)
Our study evaluated relationships between two surrogate measured vital capacity and aerobic capacity of predict Anthropometric Characteristics Determine the Cardiorespiratory Fitness among Soccer Players. Whereas our background confirms that weight-for-height as a relationship, were not considered in the kinematics analysis during the match. For the propose a total of 163 male soccer players under 17 years from the Algerian football championship participated in the present study. There VO2 max were estimated based on the formula Test Cooper (VO2 max =22.351 d (km)-11.288 (ml/min/kg)) where Vital capacity was calculating based on formula (vital capacity (ml)=(27.63-0.112 × age) × height(cm)). Based on the statistical applied. Our results confirm: 1) There is a strong positive relationship between maximal aerobic capacity and the Vital capacity, 2) Height is the most predictor of Vital capacity, 3) Height is the most predictor of the maximal aerobic capacity in the case of our sample.
https://www.omicsonline.org/open-access/height-versus-weight-which-cassel-parameter-determine-pulmonary-functions-fitness-among-the-algerians-soccer-players-2161-105X-1000353.php?aid=75251
Keywords: Height; Weight; Maximal aerobic capacity; Vital capacity; Pulmonary fitness